2020
DOI: 10.1186/s13023-020-01415-7
|View full text |Cite
|
Sign up to set email alerts
|

Best practice guidelines for management of spinal disorders in skeletal dysplasia

Abstract: Background: Disorders of the spine present a common and difficult management concern in patients with skeletal dysplasia. Due to the rarity of these conditions however, the literature, largely consisting of small, single institution case series, is sparse in regard to well-designed studies to support clinical decision making in these situations. Methods: Using the Delphi method, an international, multidisciplinary group of individuals, with significant experience in the care of patients with skeletal dysplasia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Currently, surgery is the only curative treatment option for progressive symptomatic spinal stenosis in achondroplasia [ 4 , 57 ]. However, there is no general agreement on the optimal timing for surgical intervention, although some studies have suggested a more favorable outcome if an early surgical intervention is performed after onset of symptoms [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, surgery is the only curative treatment option for progressive symptomatic spinal stenosis in achondroplasia [ 4 , 57 ]. However, there is no general agreement on the optimal timing for surgical intervention, although some studies have suggested a more favorable outcome if an early surgical intervention is performed after onset of symptoms [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Patients with MPS IV also have characteristic vertebral body beaking from the inferior half of the vertebral body (Figure 6D). 36 Because a missed or delayed MPS diagnosis may delay medical treatment, White et al 37 recommended screening for MPS when a patient with an unknown skeletal dysplasia has evidence of vertebral body beaking—this includes testing for leukocyte esterase activity and urinary glycosaminoglycans.…”
Section: Spinal Manifestations Of Skeletal Dysplasiamentioning
confidence: 99%
“…[2][3][4][5] Surgical treatment of spinal deformity is associated with increased risk of dural lesions and neurological injury in patients with skeletal dysplasia. 6 EOS is classified as idiopathic, congenital, neuromuscular, or syndromic according to the underlying cause. 7 Patients whose EOS is related to skeletal dysplasias are in the syndromic group.…”
Section: Introductionmentioning
confidence: 99%